Genesis, Evolution and Indicators of Leadership in the World Economy - Yeletsky, Alexey N. (International Journal of Criminology and Sociology, 2021)
The article reflects the results of scientific research on leadership in the world economy. The purpose of the article is to analyze the problems of determining the key factors of the genesis and evolution of this phenomenon, as well as to identify indicators of the leading position of countries in the global economy. The relevance of the topic is due to the current global processes of the structural shifts within the world economic system and trends concerning a new change in the geo-economic leadership. Based on the world-system methodology, the geo-economic approach, as well as the comparative and historical methods in economics, methods of global political economy, the author developed and demonstrated their synergic potential applied to the research of the world economy’s evolution. Heuristic possibilities of the methodological-theoretical concept of a geo-economic polarity (including multipolarity) are used. The author concludes that the leadership is characterized by the presence of immanent factors that determine the genesis of becoming a leader. It is substantiated the significance of each of these factors and proved that their effective combination leads to the formation of a leadership in the global economy. The article provides and describes the chronological periodization of leadership, and its universal triggers, which are unique for each specific stage of the world economy’s development. It is established the presence of key indicators that reflect this leadership, and emphasizes the change and expansion of the range of these indicators in the process of the evolutionary development of productive forces. It is justified that current leadership tends to geographic dispersion and is expressed in the gradual establishment of a geo-economic multipolarity of the world economy. The article predicts the current change in the nature of geo-economic leadership itself.